INOVASI KURIKULUM “MERDEKA BELAJAR” DI ERA SOCIETY 5.0 - Mira Marisa (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2021)
Policies are made on the basis of issues and considerations related to the expected goals. Technological developments will always affect human life so that they have an impact on how people think and behave in their lives.. The education sector, from time to time has developed into a polemic for individuals if a significant policy is not implemented. The data collection method from this article is carried out by using the literature study technique, in the form of reference sources from books, journals and so on. Therefore, Indonesia is currently making this breakthrough by changing the curriculum policy to be "free to learn" which is intended so that the policy does not burden education both for educators and students. The policy of independent learning is intended to make the learning process more enjoyable and less boring. The independent learning curriculum is also expected to be able produce output from education who have high morals. That the independent learning curriculum strives for the role of technology, which is a human need today, to be integrated with another. So, in the era of society 5.0 problems of social life experienced by each individual will be combined with the role of technology which is used as a tool in solving problems of social life.